HALAL PERSPECTIVE: A CONCEPT PROMOTION CULINARY THROUGH DIGITAL MARKETING TO IMPROVE SMEs PERFORMANCE IN BATAM - Kurniawan, Putu Hari; Lismayasari, Lismayasari; Novrianti, Dian Puspita (Universitas Brawijaya, Indonesia, 2020)
This study aims to provide stimulants to the leading sectors contributing to the state budget from the non-oil and gas sector. So far, tourism has an extraordinary strategic function in terms of food healthy and job creation for the community. the objectives are to explore whether SMEs have procedures related to digital marketing to promote halal culinary in Batam which this situation can influence the SMEs growth sustainable, how come 65% of the economic contribution in Indonesia is contributed by SMEs based on home industries. Batam is a special economic zone that has tremendous potential in tourism development. The strategic location close to the economic center of ASEAN, Singapore, provides benefits for tourism development, currently especially related to culinary tourism. Culinary and tourism is an identity culture to introduce the potential of an area to the outside community. In this study, as researchers, we investigate the existence of digital marketing as SMEs accommodation in promoting halal culinary products through social media, search engine marketing, and online websites. Data collected sample from the consumers who bought halal food for SME production in Batam amount of 160 respondents where investigate with the Cluster sampling method. This study is explanatory research to released the problem of data with Structure Equation Model (SEM) analysis to solve the problems that cannot be answered in previous studies. Contribute to SME's scope in future research, deep subjectivity is needed related to segmentation, culture, and religious dogma.